ANCESTRAL GASTRONOMIC KNOWLEDGE AND CULTURAL TOURISM OF THE CITY OF RIOBAMBA, PROVINCE OF CHIMBORAZO - Guevara, Michael Roberth Villalva (2021)
The paper analyzes the cultural richness in food dwelling in Ecuadorian gastronomy, which has been relegated to a complementary plane in the national touristic service for years. This documentary review aimed to analyze the ancestral gastronomic knowledge to promote cultural tourism in Riobamba city through agro-tourism, traditional festivities, customs, and local gastronomy. The bibliographic review method and the selection of the information were used by means of documentary inclusion and exclusion criteria in the analysis of 153 manuscripts. By employing criteria of relevance and exhaustiveness, 27 cataloged articles of greater relevance were chosen. Subsequently, events, interactions, attitudes, and behaviors were analyzed by utilizing qualitative techniques. It was demonstrated that the Riobamba city has significant cultural manifestations bonded to gastronomy, which include ancestral knowledge, culinary practices, rituals, and beliefs that, in conjunction with the cultural empowerment of citizens and culinary projects in the public sector, can exponentially improve local gastronomic tourism.